Communication Patterns in Editorial Management at ITB Press Bandung - Gun Gun Waldi Gumilar; Sulistiyo Wibowo; Andrian Andrian (2022)
This research aims to determine the effectiveness of implementing communication patterns in editorial management at ITB Press, a university book publisher within the Bandung Institute of Technology (ITB). Using descriptive writing, the researchers describe the editorial management communication pattern at ITB Press. Based on observations of the work steps carried out at ITB Press, it is proven that all manuscripts are monitored for their existence, complete with authors and the statusÂ ofÂ the publishing work process at the time of recording. The conclusion is that the editorial management communication pattern carried out at ITB Press has been running effectively as expected. However, ITB Press should continue to develop, improve, and perfect the system, if necessary, in accordance with the demands of the times and technology, to make all of its work more effective.